EFEKTIVITAS PENGELOLAANN DANA BAZNAZ MELALUI PENERAPAN METODE ESG SYARIAH (STUDI BAZNAS KOTA PROBOLINGGO) - Reza Hilmy Luayyin; Kharisma Apriliya; M. Nabat Ardli (Wasīlah: Journal Of Sharia Sciences, 2025)
This study aims to analyze the effectiveness of BAZNAS Kota Probolinggo’s governance through the application of the Shariah-based ESG method, which integrates the Environmental, Social, and Governance dimensions within an Islamic compliance framework. As an official zakat management institution, BAZNAS faces increasing demands for transparency, accountability, and sustainable program implementation, in line with the development of Islamic social finance that emphasizes sustainability and public welfare. This research employs a qualitative descriptive approach through field observations, in-depth interviews, and institutional document reviews. The findings indicate that the Environmental dimension has been addressed through various environmental initiatives; however, the absence of measurable performance indicators limits its overall effectiveness, placing it at a moderate level. The Social dimension demonstrates the highest level of effectiveness, reflected in accurate zakat distribution, economic empowerment programs, and inclusive community engagement. Meanwhile, the Governance dimension also shows strong performance due to solid accountability mechanisms, transparent reporting, and adherence to Shariah principles, although improvements in digital monitoring systems remain necessary. Overall, the application of the Shariah-based ESG method enhances the governance quality of BAZNAS Kota Probolinggo and strengthens its role as a sustainable Islamic philanthropic institution that responds effectively to community needs. Keywords: BAZNAS, Zakat, Fund Diversification, Welfare, Economic Empowerment.